Smart Greenhouse Based on IoT Application - Rosni, Muhammad Muqri; Hashim, Hairulazwan (Progress in Engineering Application and Technology, 2021)
Control systems have in recent days modified and introduced irrigation to meet the needs of people. Getting determined the amount of irrigation needed is a complicated process and many important factors must be taken into account. This paper provides an efficient automatic irrigation system based on the use of wireless network and the server and client’s web service as the basis for computing and monitoring various changes required in green house. The two key factors in our model are power reduction, control and monitoring over long distances. The results show that the control model analyses the sensing data and the specific method for measuring the values of adapted sensors and also the self-controlling of the output linked equipment. The findings also show that our system has many beneficial properties such as simple management of network and controlling motors. In the proposed design method, four sensors are adaptable to monitor environmental changes within the greenhouse, such as soil moisture , humidity , temperature and light sensor. Since irrigation begins often when different depletion ratios of all sensors are available to operate plugged devices for different operations.